1989
DOI: 10.1152/jappl.1989.66.5.2079
|View full text |Cite
|
Sign up to set email alerts
|

Site of recruitment in the pulmonary microcirculation

Abstract: Increasing the total surface area of the pulmonary blood-gas interface by capillary recruitment is an important factor in maintaining adequate oxygenation when metabolic demands increase. Capillaries are known to be recruited during conditions that raise pulmonary blood flow and pressure. To determine whether pulmonary arterioles and venules are part of the recruitment process, we made in vivo microscopic observations of the subpleural microcirculation (all vessels less than 100 microns) in the upper lung wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

1992
1992
2015
2015

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 0 publications
2
24
0
Order By: Relevance
“…Second, as the result of this distensibility, the pulmonary microvasculature, or capillary segment, is the locus of such changes in flow and/or volume (Glazier et al, 1969;Wagner and Latham, 1975;West et al, 1975;Capen et al, 1981Capen et al, , 1987Capen and Wagner, 1982;Hanson et al, 1989;Warrell et al, 1972). This finding correlates well with studies that indicate that the compliance or capacitance of the pulmonary vasculature is located in this same vascular segment.…”
Section: Vessel Recruitment Versus Distensionsupporting
confidence: 74%
See 1 more Smart Citation
“…Second, as the result of this distensibility, the pulmonary microvasculature, or capillary segment, is the locus of such changes in flow and/or volume (Glazier et al, 1969;Wagner and Latham, 1975;West et al, 1975;Capen et al, 1981Capen et al, , 1987Capen and Wagner, 1982;Hanson et al, 1989;Warrell et al, 1972). This finding correlates well with studies that indicate that the compliance or capacitance of the pulmonary vasculature is located in this same vascular segment.…”
Section: Vessel Recruitment Versus Distensionsupporting
confidence: 74%
“…Essentially, these studies demonstrated that as the flow through the pulmonary circulation increased during exercise, so did the diffusing capacity for carbon monoxide. This finding suggested that a larger circulatory bed was being perfused and that the recruitment of previously closed vessels had occurred (Permutt et al, 1969;Wagner and Latham, 1975;West et al, 1975;Wagner et al, 1979;Capen et al, 1981Capen et al, , 1987Capen and Wagner, 1982;Hanson et al, 1989).…”
Section: Vessel Recruitment Versus Distensionmentioning
confidence: 96%
“…Additionally, changes in D M track changes in Vc, although it is likely that correcting D M for Vc (D M /Vc) should accurately estimate changes in D M and, therefore, lung water. Finally, increases or decreases in forced vital capacity (FVC) and maximal expiratory flow rates should follow changes in either thoracic blood volume or lung water.Typically, exposure to hypoxia causes an increase in DL CO , which is caused, at least in part, by an increase in Vc (12,13,19,20,22,62,64). The increase in Vc with hypoxia is a result of elevations in pulmonary pressure caused from heterogenous pulmonary vasoconstriction (64, 65).…”
mentioning
confidence: 99%
“…Others have directly demonstrated the capacity to recruit pulmon-4. Discussion ary capillaries using in vivo video-microscopy during conditions that raise pulmonary blood flow and pressure This study was designed to determine if pulmonary [15]. Our data therefore demonstrate that in conditions of clearance of circulating ET-1 is altered by tachycardiaapparent maximal recruitment of the pulmonary vascular induced CHF.…”
Section: Effect Of Flow On Et-1 Metabolism In Isolated Ratmentioning
confidence: 77%